pH-responsive self-assembly of quercetin-loaded zein-sodium caseinate-fucoidan hybrid nanoparticles: nanostructure, stability and in vitro digestive behavior - Yong, Fan-Xing; Deng, Jia-Xin; Wang, Zhuo; Zhao, Qiao-Li; Liu, Xiao-Fei; Zhong, Sai-Yi; Li, Rui (Frontiers in Nutrition, 2026)
IntroductionQuercetin (Que), a physiologically versatile flavonoid, faces application limitations in food and pharmaceuticals due to poor aqueous solubility and stability.MethodTo address this, we developed quercetin-loaded zein-sodium caseinate-fucoidan (Que-ZE-SC-FD) ternary nanoparticles using a green, pH-driven approach.Results and discussionThe Que-ZE-SC-FD nanoparticle exhibited a spherical morphology stabilized by hydrogen bonding, electrostatic, and hydrophobic interactions, with a mean diameter of 137.8 ± 11.6 nm, PDI of 0.38 ± 0.04, z-potential of 34.9 ± 0.6mV, and high quercetin loading efficiency (92.8% ± 1.1%). Crucially, SC and FD demonstrated synergistic stabilization effects. The Que-ZE-SC-FD nanoparticle exhibited a mean particle size of 150.8 ± 0.6 nm at a pH of 8.0, and solution remained clear and transparent with no observable sediment. Under a NaCl concentration of 3.0 mol/L, the particle size decreased to 127.8 ± 4.5 nm. Upon heating at 80°C for 2 h, the particle size further reduced to 121.3 ± 1.2 nm, with a PDI of 0.34 ± 0.02. After 28 days of storage, the particle size decreased to 125.1 ± 1.9 nm, while the PDI decreased slightly to 0.32 ± 0.01 and the zeta potential increased to 31.6 ± 1.5mV, collectively indicating excellent stability. Under simulated gastrointestinal conditions, the Que release from ZE-SC-FD nanoparticles was only 22.2 ± 0.5% in gastric fluid; however, a significantly higher release rate of 75.0 ± 0.5% was achieved in intestinal fluid. These results demonstrate that ZE-SC-FD nanoparticles serve as a robust nanocarrier system for encapsulating, protecting, and delivering quercetin.